Cooperation in Turbulent Times: Strategies of Jews and Muslims in Amsterdam. Issue 3 (3rd July 2017) - Roggeveen, Suzanne; Vellenga, Sipco J.; Wiegers, Gerard A.
ABSTRACT: Relations between Jews and Muslims in Amsterdam grew tense after the conflicts between Gaza and Israel in 2014, the violent attacks on Jewish targets in Brussels (2014), Paris (2015) and Copenhagen (2015) and local incidents of online, verbal and sometimes physical discrimination. Nevertheless, these factors also inspired Jews and Muslims to launch cooperation projects and strengthen the bonds already existing between them. Cooperation in turbulent times is not always easy. The data collected for this research show how Jews and Muslims in cooperation projects use to strategies to solve some of the problems confronting them. The three most widely used strategies that were found are 'searching for similarities', 'decategorizing' and 'avoidance'. These strategies do not emerge in a vacuum, however, but at a certain moment in time, in specific fields. Therefore, this article, will describe the usage of the three strategies and explain the interaction between strategies and their contexts.